The Knowledge and Compliance of Fluid Restriction of Heart Failure Patients in Hospital - Istiroha, Istiroha; Suryaningsih, Iis; Revita, Natalia Christin Tiara (Universitas Muhammadiyah Lamongan, 2025)
Introduction: Fluid overload is a classic clinical picture of patients with heart failure. The implementation of this fluid restriction requires compliance from the patient. One of the factors that influence compliance is knowledge. This study aims to describe the knowledge and compliance of fluid restriction in patients with heart failure. Methods: This study used an analytic descriptive design. The population in the study were heart failure patients in the Gardena Room of Ibnu Sina Gresik Hospital in July 2024 as many as 30 people. A sample of 28 people was taken with purposive sampling technique. Data collection using questionnaires and observation sheets. The collected data were processed and analyzed using bivariate analysis with SPSS program. Results: The results showed that respondents were mostly male (64.3%), between 46 and 55 years old (46.4%), worked as farmers (32.1%), junior high school garduate (42.9%), and had suffered from heart failure for ≤ 1 (50%). The most of the respondents' knowledge about fluid restriction was in the low category (57.1%) and patient compliance in fluid restriction was in the non-compliant category (78.6%), Conclusion: Many heart failure patients do not know and do not comply with fluid restriction. The hospital should make policies and health education media to improve the knowledge and compliance of heart failure patients in fluid restriction